Impact of valproate and levetiracetam exposure on GAERS behavior during pregnancy - TURGAN AŞIK, ZEHRA NUR; KOYUNCUOĞLU, TÜRKAN; KASIMAY ÇAKIR, ÖZGÜR (My University, 2023)
Objective: Valproate (VPA) and levetiracetam (LEV) are frequently prescribed for the management of idiopathic generalized seizures; however, their well-documented teratogenic effects raise concerns when administered to pregnant epileptic patients. This study aimed to assess the impact of VPA and LEV exposure during pregnancy on Genetic Absence Epilepsy Rats from Strasbourg (GAERS). Methods: Female GAERS rats were categorized into three groups: saline-treated (n=6), VPA-treated (200 mg/kg, n=4), and LEV-treated (50 mg/kg, n=6). Intraperitoneal injections were initiated from mating start and continued until partition. Locomotor activity and anxiety-like behavior were evaluated using open-field and hole-board tests for the VPA-treated and VPA-and LEV-treated groups; respectively. These tests were conducted both before and during pregnancy. Results: Across all groups, open-field testing demonstrated a tendency toward reduced locomotor activity parameters compared with pre-pregnancy, with VPA treatment showing significance (p<0.05). The hole-board test indicated a trend toward decreased rearing and hole exploration, coupled with increased freezing behavior in the saline-and VPA-treated groups. The LEV-treated group showed an elevation in freezing behavior and a decline in hole exploration. Conclusion: Although minimal effects on anxiety-like behaviors were noted in anti-seizure drug-treated rats, subtle tendencies were evident in the hole-board test. VPA and LEV administration resulted in depressive parameters in the locomotor activity test. These findings emphasize the need for caution when prescribing and using VPA and the LEV during pregnancy in terms of maternal behavior and mood.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Neurology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; CLINICAL NEUROLOGY; Nöroloji (klinik); Yaşam Bilimleri; Neurology (clinical); Life Sciences; GAERS; levetiracetam; maternal behavior; pregnancy; valproic acid